Peran Mediasi Brand Satisfaction Pada Pengaruh Self Congruity Terhadap Brand Loyalty - Dedek Kurniawan Gultom; Muhammad Arif; Muhammad Elfi Azhar; Mukmin Mukmin (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study aims to produce a Brand Loyalty Improvement Model Based on Brand Satisfaction and Self Congruity of Iphone Users in Medan City. The population in this study were iPhone users in Medan City. The sampling technique was non-probability sampling, while the sample was set at 125 people. Data collection techniques used were interviews (Interview) and a list of questions (Questionaire). The data analysis method used in this research is the Structural Equation Model method. The results showed that Actual Self affects Brand Satisfaction, Actual Self affects Brand Loyalty, Ideal Self affects Brand Satisfaction, Ideal Self affects Brand Loyalty, Brand Satisfaction affects Brand Loyalty. Brand Satisfaction can positively mediate the influence of Actual Self on Brand Loyalty and Brand Satisfaction can positively mediate the influence of Ideal Self on Brand Loyalty.